Prognostic Value of the Number of Removed Lymph Nodes in Vulvar Squamous Cell Carcinoma Patients With Node-Positive Disease: A Population-Based Study - Wu, San-Gang; Zhang, Wen-Wen; Sun, Jia-Yuan; Chen, Qiong-Hua; He, Zhen-Yu; Zhou, Juan (Frontiers in Oncology, 2018)
Introduction: To investigate the effect of the number of removed lymph nodes (RLNs) on outcomes in patients with node-positive vulvar squamous cell carcinoma (SCC). Methods: This population-based retrospective study included vulvar SCC patients recorded on the Surveillance, Epidemiology, and End Results database who received surgery and lymphadenectomy. Cox regression proportional hazards was used for multivariate analysis. The number of RLNs was examined as a 4-level categorical variable based on quartiles. Results: In total, 703 patients were identified. Patients with a higher RLN count had a significantly higher number of positive lymph nodes. The 3-year cause-specific survival (CSS) rates were 48.9%, 65.9%, 73.1%, and 67.3% in patients with 1–6, 7–10, 11–16, and 17–45 RLNs, respectively (p < 0.001), and the 3-year overall survival (OS) rates were 36.1%, 50.6%, 61.1%, and 57.6%, for the same RLN groups, respectively (p < 0.001). RLN count was an independent predictor of outcome. Using 7–10 RLNs as reference, patients with 1–6 RLNs had poor CSS (hazard ratio [HR] 1.727, 95% confidence interval [CI] 1.201–2.485, p = 0.003) and OS (HR 1.436, 95% CI 1.078–1.911, p = 0.013), while there were comparable outcomes in patients with 11–16 and 17–45 RLNs to patients with 7–10 RLNs. Adjuvant radiotherapy improved CSS (p = 0.023) and OS (p = 0.003) in patients with ≤6 RLNs, but was not associated with better outcomes in patients with >6 RLNs. Conclusions: The removal of more than 6 lymph nodes improves vulvar SCC outcomes in patients with node-positive disease.